Cancer treatment-related cardiac dysfunction. Issue 1 (26th July 2022) - Brady, Bernadette; Murphy, Ross
Abstract : Objectives: This paper describes cardiotoxicity and cancer treatment-related cardiac dysfunction (CTRCD). Long-term sequelae of treatment are important, and changing, and may manifest when a patient is under the care of a supportive care service. Methods: Key messages for supportive and palliative care clinicians are outlined to facilitate identification and management of CTRCD. Results: Not all cardiotoxicity is alike. Types of cardiotoxicity, cardiac complications of immunotherapy, the challenge of autonomic nervous system dysfunction in cancer and management of cardiotoxicity are highlighted. Conclusions: The key strategies are early detection of cardiotoxicity, monitoring for development of CTRCD during treatment and surveillance in survivorship.